2017
DOI: 10.1007/s13142-016-0459-8
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an evidence-based biobehavioral treatment for cancer patients

Abstract: One aim of dissemination and implementation (DI) research is to study the translation of evidence-based treatments (EBTs) from the research environments of their development and testing to broader communities where they are needed. There are few behavioral medicine DI studies and none in cancer survivorship. A determinant model (Setting, Therapist, Education, imPlementation, and Sustainability (STEPS)) was used to conceptualize DI of mental health treatment and frame a longitudinal study of implementation of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 69 publications
(80 reference statements)
0
7
0
Order By: Relevance
“…Therapists’ BBI usage was impressive; the proportion of therapists’ patients treated with BBI ranged from 58% to 68% across 2-, 4-, and 6-month follow-ups, with additional data showing sustained usage at 12 months (71%). As predicted by STEPS, both therapists’ positive attitudes toward BBI and setting factors (supervisors’ positive attitudes) were associated with usage (Ryba, Brothers, & Andersen, 2017).…”
Section: Path T1: Biobehavioral Model Of Cancer Stress and Disease Co...mentioning
confidence: 78%
See 1 more Smart Citation
“…Therapists’ BBI usage was impressive; the proportion of therapists’ patients treated with BBI ranged from 58% to 68% across 2-, 4-, and 6-month follow-ups, with additional data showing sustained usage at 12 months (71%). As predicted by STEPS, both therapists’ positive attitudes toward BBI and setting factors (supervisors’ positive attitudes) were associated with usage (Ryba, Brothers, & Andersen, 2017).…”
Section: Path T1: Biobehavioral Model Of Cancer Stress and Disease Co...mentioning
confidence: 78%
“…All of the latter, however, came from the same research group with no effectiveness tests by others. Overall, we were aware of the high uptake of BBI (Ryba et al, 2017), but neither the fidelity of therapists' implementations nor impact of BBI on patient outcomes was known. Another condition of the Type II design is conduct when there is "implementation momentum."…”
Section: Discussionmentioning
confidence: 99%
“…The use of less formal gatherings aimed at educating stakeholders included, for example, “ addressing the subject informally during lunch breaks ” (Aasekjær et al, 2016, p. 35), offering one-to-one tutoring (Bice-Urbach & Kratochwill, 2016; Kaasalainen et al, 2015), integrating educational elements into an agency’s routine staff meeting (Byrnes et al, 2018; Graaf et al, 2017), or initiating ad hoc informal training sessions upon request by those supported (Tierney et al, 2014). Study reports that presented the techniques used to educate stakeholders in these meetings reflected a consistent combination of didactic and dynamic, interactive teaching elements (Becker et al, 2013; Beidas et al, 2012; Brownson et al, 2007; Chaffin et al, 2016; Dobbins et al, 2018; Ryba et al, 2017; Tierney et al, 2014; Yano et al, 2008), the latter of which typically aimed at integrating the concrete and individual/local work experience of those supported.…”
Section: Resultsmentioning
confidence: 99%
“…(2) Discussion of strategies for therapists to address implementation barriers was provided 8 . (3) Usage by the newly trained providers was high—ranging from 59 to 68% of provider's patients receiving the BBI from 2 to 6 months, 9 with usage sustained (73%) at 12‐months, one year post institute 10 . (4) Providers' changes (improvements) in attitudes and intent during dissemination predicted usage, 9,11 and providers' gains in self‐efficacy to deliver the BBI and positive attitudes about using evidence based treatments were discovered as mechanisms for achieving implementation 5,7 .…”
mentioning
confidence: 99%
“…8 (3) Usage by the newly trained providers was high-ranging from 59 to 68% of provider's patients receiving the BBI from 2 to 6 months, 9 with usage sustained (73%) at 12-months, one year post institute. 10 (4) Providers' changes (improvements) in attitudes and intent during dissemination predicted usage, 9,11 and providers' gains in self-efficacy to deliver the BBI and positive attitudes about using evidence based treatments were discovered as mechanisms for achieving implementation. 5,7 (5) Finally, a multi-site (n = 15) hybrid study showed providers (N = 15) delivered the BBI with fidelity comparable to that of the BBI efficacy trial (see below), consistent with patient (N = 158) reports of BBI component usage, and moreover, BBI treated patients significantly improved in mood and physical activity.…”
mentioning
confidence: 99%